Preparation method of sulfur-doped near-infrared carbonized polymer for detecting mercury ions and its detection application
By using sulfur-doped near-infrared carbonized polymer (r-CPDs-S) for fluorescence colorimetric detection, the rapid, real-time and economic problems of trace Hg2+ detection in water environments in the prior art are solved, and mercury ion detection with high selectivity and sensitivity is achieved.
Patent Information
- Application Number
- CN202411624957.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The prior art is difficult to achieve rapid, real-time and economical detection of trace Hg2+ in water environments. Traditional methods require tedious sample preprocessing and expensive large-scale instruments.
Mercury ions were detected by fluorescence colorimetric method using sulfur-doped near-infrared carbonized polymer (r-CPDs-S), and Hg2+ was chelated by disulfide bond groups formed by 4-aminothiophenylthiophenol to achieve a specific fluorescence response.
It realizes high selectivity and highly sensitive detection of trace mercury ions, is not susceptible to interference from external environmental factors, and can complete rapid detection and on-site real-time monitoring of mercury-containing ions without the need for professional large-scale instruments.
Smart Images

Figure CN119160880B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a mercury ion detection method, in particular to a preparation method of a sulfur-doped near-infrared carbonized polymer for detecting mercury ions and a detection application thereof. Background Art
[0002] Mercury (Hg) as one of the heavy metals has a wide range of applications in industry and science, such as in thermometers, electronic equipment, reactors, chemical synthesis and metal replacement. Mercury exists mainly in three forms, including elemental mercury, organic mercury and inorganic mercury. Among them, mercury is difficult to degrade in the environment, while inorganic mercury compounds can be converted into organic mercury such as methylmercury in water bodies, which are easily absorbed in organisms, can be accumulated through ecosystems, and transferred to the human body through the food chain. Even at the ppm level, the mercury accumulated in the body cannot be eliminated from the body through its own metabolism, which directly has a negative impact on the human nervous system, kidneys, heart, brain, lungs and immune system, posing a potential threat to human health and the aquatic environment. Therefore, it is necessary to establish trace Hg in the water environment. 2+ A rapid detection method is urgently needed.
[0003] Currently, Hg 2+ The conventional detection methods of mercury mainly include atomic absorption spectroscopy, inductively coupled plasma mass spectrometry, anodic stripping voltammetry and high performance liquid chromatography. Among them, inductively coupled plasma mass spectrometry has the advantages of high detection limit, high sensitivity and fast analysis speed, making it the main means of mercury detection. Although conventional analytical methods perform well in the laboratory, the operation process usually requires cumbersome sample pretreatment and the use of expensive large instruments, which is not suitable for on-site real-time monitoring. Anodic stripping voltammetry requires a complex enrichment and dissolution process, and relies on equipment such as electrodes and power supplies. It is not convenient for on-site real-time detection, which limits its scope of application. Therefore, it is necessary to research and develop methods that are convenient for on-site real-time monitoring of Hg 2+ A simple, economical and fast-response detection method for ions is crucial.
[0004] Carbon dots (abbreviated as CQDs) are a type of carbon-based nanoparticles with a size less than 10nm and a complex structure. This type of material includes carbon quantum dots (CQDs), graphene quantum dots (GQDs) and carbonized polymer dots (CPDs). Near-infrared CPDs are a type of carbon dots that have rich active groups and are highly chemically tunable. They have been widely used in chemical sensing, bioimaging and catalysis. Secondly, these CPDs are highly stable and show excellent optical stability. Compared with traditional blue and green light carbon dots, they show low background noise and strong anti-interference in various environments, and are particularly suitable for the detection of heavy metals in water environments. At present, there is no public research report on the preparation method of near-infrared carbonized polymers for detecting trace mercury ions and their detection applications. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method of a sulfur-doped near-infrared carbonized polymer for detecting mercury ions with strong stability, good selectivity, high sensitivity and accuracy, and detection application thereof.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a preparation method of a sulfur-doped near-infrared carbonized polymer for detecting mercury ions, the specific steps are as follows: 1-4 mmol o-phenylenediamine, 1 mmol trimesic acid and 1-4 mmol 4-aminothiophenol are dissolved in 12 mL of deionized water, and then 200-600 μL of concentrated sulfuric acid is added, and after ultrasonication at 40 Hz for 2-3 min, it is transferred to a polyethylene tetrafluoro liner, and then placed in an autoclave, heated at 200-230° C. for 6-8 h, after the reactor is naturally cooled to room temperature, a 1000 Da dialysis bag is used to perform uninterrupted dialysis for 24-48 h to remove unreacted impurities, and then placed at a temperature of -20-30° C. and a pressure of -0.1-0.01 Pa for freeze drying for 24-48 h to obtain black particles, which are the sulfur-doped near-infrared carbonized polymer for detecting mercury ions.
[0007] Preferably, the molar mass ratio of the o-phenylenediamine, the trimesic acid and the 4-aminothiophenol is 3:1:2.
[0008] Preferably, the amount of concentrated sulfuric acid added is 400 μL.
[0009] The present invention also provides a method for detecting mercury ions using the sulfur-doped near-infrared carbonized polymer prepared by the above method, comprising the following steps: adding an r-CPDs-S solution with a concentration of 10 to 40 mg / L and a sample solution to be tested into a cuvette filled with ethanol, setting the pH of the mixed solution in the cuvette to 6 to 10 and the salinity to 20 to 40‰, detecting the fluorescence intensity values before and after the r-CPDs-S solution is added to the sample solution to be tested at an excitation wavelength of 530 nm, and recording them as F0 and F1 respectively, and calculating the fluorescence intensity of the r-CPDs-S solution according to the Hg concentration. 2+ The linear relationship between the concentration and the fluorescence intensity ratio F0 / F is used to calculate the Hg in the sample solution to be tested. 2+ The concentration of r-CPDs-S solution, the test sample solution and the ethanol is in a volume ratio of 1:1:98.
[0010] Preferably, the concentration of the r-CPDs-S solution is 10 mg / L.
[0011] Preferably, the pH of the mixed solution in the cuvette is 7 and the salinity is 25‰.
[0012] Compared with the prior art, the advantages of the present invention are as follows: the present invention discloses a preparation method of a sulfur-doped near-infrared carbonized polymer for detecting mercury ions and its detection application, and the disulfide bond groups formed by 4-aminobenzenethiophenol are used to detect Hg 2+ Chelation to achieve Hg 2+ The sulfur-doped near-infrared carbonized polymer can quantitatively analyze trace mercury ions by fluorescence colorimetry. It has good selectivity and highly sensitive detection capabilities, is not easily interfered by external environmental factors, and ensures the reliability of detection. It can also complete the rapid detection of mercury ion-containing analytes without the help of professional large-scale instruments, which not only effectively solves the high cost problem of traditional detection methods, but also can achieve trace Hg 2+ On-site real-time monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The structural characteristic diagram of the sulfur-doped near-infrared carbonized polymer (abbreviated as r-CPDs-S) prepared by the method of the specific embodiment 1, wherein A is the transmission electron microscope image and lattice of r-CPDs-S, and B is the infrared absorption spectrum of r-CPDs-S;
[0014] Figure 2 The XPS spectrum scan of r-CPDs-S prepared by the method of the specific embodiment 1, wherein A is the C1s peak, B is the N1s peak, C is the O1s peak, D is the S2p peak, Raw is the refitted peak, Fitted is the fitted peak, Background is the background noise, pyridinic-N is pyridine-N, and Secondary amine is secondary nitrogen;
[0015] Figure 3 In the specific embodiment 2, Hg is added 2+ XPS spectrum scanning diagram of r-CPDs-S, where A is C1s peak, B is N1s peak, C is O1s peak, D is S2p peak, Raw is refitted peak, Fitted is fitted peak, Background is background noise, pyridinic-N is pyridinic-N;
[0016] Figure 4 Add Hg to r-CPDs-S in Example 2 2+ Changes in fluorescence properties before and after, where A is r-CPDs-S and r-CPDs-S / Hg 2+ UV absorption spectra of r-CPDs-S and r-CPDs-S / Hg 2+ Differential pulse voltammetry diagram, C is r-CPDs-S and r-CPDs-S / Hg 2+ Fluorescence spectra of r-CPDs-S and r-CPDs-S / Hg 2+ The transient fluorescence lifetime results;
[0017] Figure 5 This is the detection condition optimization experiment of r-CPDs-S for detecting mercury ions in the specific embodiment 3, wherein A is the fluorescence intensity ratio of r-CPDs-S in different solvents, B is the fluorescence intensity ratio at different r-CPDs-S concentrations, C is the fluorescence intensity ratio of r-CPDs-S at different pH values, D is the fluorescence intensity ratio of r-CPDs-S at different water contents in ethanol, E is the fluorescence intensity ratio of r-CPDs-S at different salinities, and F is the fluorescence intensity ratio of r-CPDs-S at different excitation wavelengths;
[0018] Figure 6 is the optimization result of the synthesis conditions of r-CPDs-S in the specific embodiment 4, wherein A is the fluorescence intensity ratio of r-CPDs-S synthesized with different proportions of o-phenylenediamine, trimesic acid and 4-aminothiophenol, B is the fluorescence intensity ratio of r-CPDs-S synthesized with different amounts of concentrated sulfuric acid added, and C is the fluorescence intensity ratio of r-CPDs-S synthesized with different heating times;
[0019] Figure 7 The selectivity experimental results of r-CPDs-S in the specific embodiment 5, wherein A is the effect of different metal ions on the fluorescence response of r-CPDs-S, and B is the effect of metal cations on r-CPDs-S / Hg 2+ The fluorescence quenching effect of different anions on r-CPDs-S, C is the effect of different anions on the fluorescence response of r-CPDs-S, and D is the effect of different anions on r-CPDs-S / Hg 2+ The fluorescence quenching effect of
[0020] Figure 8 The fluorescence color change (A) of the r-CPDs-S solution after adding different metal ions under 365 nm ultraviolet light and the color change (B) under sunlight;
[0021] Fig. 9 In the specific embodiment 6, different concentrations of Hg are added. 2+ The fluorescence intensity change of r-CPDs-S (A) and the fluorescence intensity ratio with Hg 2+ Linear regression curve of concentration (B);
[0022] Fig.10 In the specific embodiment 6, different concentrations of Hg are added. 2+ Color change of r-CPDs-S solution under sunlight irradiation (A) and fluorescence color change under 365 nm UV light irradiation (B). DETAILED DESCRIPTION
[0023] The present invention is further described in detail below with reference to the accompanying drawings.
[0024] Specific embodiment 1, a method for preparing a sulfur-doped near-infrared carbonized polymer for detecting mercury ions, the specific steps are as follows:
[0025] 3mmol o-phenylenediamine, 1mmol trimesic acid and 2mmol 4-aminothiophenol were dissolved in 12mL of deionized water, and 400μL of concentrated sulfuric acid was added. After ultrasonic treatment at 40Hz for 2-3min, the mixture was transferred to a 15mL polyethylene tetrafluoroethylene liner and placed in an autoclave. After heating at 200-230℃ for 6-8h, the autoclave was naturally cooled to room temperature. Black particles were observed to form in the solution. After continuous dialysis for 24-48h using a 1000Da dialysis bag to remove unreacted impurities, the mixture was freeze-dried for 24-48h at a temperature of -20-30℃ and a pressure of -0.1-0.01Pa to obtain black particles, which were sulfur-doped near-infrared carbonized polymers (abbreviated as r-CPDs-S) for detecting mercury ions. Figure 1 Figure 2 shows the structure of sulfur-doped near-infrared carbonized polymer.
[0026] Depend on Figure 1 From the transmission electron microscopy image of r-CPDs-S in Figure A, we can see that the particle size of r-CPDs-S is 10~20 nm and the lattice is 0.21 nm. Figure 1 The infrared absorption spectrum of r-CPDs-S of B in the -1 and 3080 cm -1The broad characteristic peaks at 2920 cm -1 The characteristic peak at 1705cm is related to the stretching vibration of =CH. -1 The characteristic peak at 1630 cm -1 The characteristic peak at 1228 cm -1 The characteristic peak at 1100 cm -1 The characteristic peak at is the stretching vibration peak of CS. The carbon and nitrogen functional groups are derived from the condensation reaction between o-phenylenediamine and trimesic acid, while the sulfur doping is derived from 4-aminothiophenol.
[0027] Figure 2 is the XPS spectrum scan of r-CPDs-S. Figure 2 From the C1s peak analysis of A in the figure, the absorption peaks of CC, C=C, CN and CO / C=O bonds of r-CPDs-S correspond to 284.72 eV, 288.85 eV, 287.74 eV and 288.76 eV respectively. Figure 2 From the N1s peak analysis of B in r-CPDs-S, we can see that the secondary amine (-NH-) and pyridine nitrogen of r-CPDs-S correspond to the absorption peaks at 398.53 eV and 400.22 eV, respectively. Figure 2 From the O1s peak analysis of C in the graph, we can see that the absorption peaks of C=O and C-OH / COC bond correspond to 531.22 eV and 532.79 eV respectively. Figure 2 The S2p peak of D in the middle shows that S2p 3 / 2 、S2p 1 / 2 and SO x These correspond to the absorption peaks at 163.39 eV, 164.60 eV and 168.50 eV, respectively.
[0028] Specific Example 2: Detection of Hg by r-CPDs-S prepared by the method of Specific Example 1 2+ Capacity analysis.
[0029] Experimental method: Prepare 10 mL of 10 mg / mL r-CPDs-S solution, add 50 μL of 10 nM Hg 2+ When the reaction shows an obvious color change from red to colorless, the reaction product is freeze-dried to obtain black particles r-CPDs-S / Hg 2+ The blank sample is the one without Hg added 2+ The black particles r-CPDs-S were obtained, and the above two solids were subjected to XPS analysis. Figure 3 Shown the addition of Hg2+ The chemical bond changes of r-CPDs-S.
[0030] Depend on Figure 3 From A in Figure 1, we can see that the binding energy of the chemical bond of the C1s peak has hardly changed. Figure 3 The N1s peak of B shows that the addition of Hg 2+ The 400.22 eV absorption peak of r-CPDs-S after addition of Hg 2+ Compared with the former r-CPDs-S, the binding energy of secondary nitrogen disappears; Figure 3 The O1s peak of C in the solution shows that 531.65 eV corresponds to C=O, which is consistent with the addition of Hg 2+ Compared with the former r-CPDs-S, the binding energy of C-OH / COC disappears; Figure 3 The S2p peaks of D in the figure show that the absorption peaks at 169.70 eV, 168.45 eV, 163.85 eV and 162.85 eV correspond to C-SO4, C-SO3, S2p, respectively. 1 / 2 and S2p 3 / 2 .
[0031] To further verify the Hg 2+ To study the effect of r-CPDs-S on the fluorescence performance, 10 mL of 10 mg / mL r-CPDs-S solution was prepared, and 50 μL of 50 nM Hg 2+ The blank sample is the one without adding Hg 2+ The above two solutions were subjected to differential pulse voltammetry, UV absorption spectroscopy, fluorescence spectroscopy scanning and transient fluorescence lifetime analysis. The results are as follows Figure 4 As shown,
[0032] Depend on Figure 4 As can be seen from A, adding Hg 2+ Before and after, the absorption peak of r-CPDs-S at 576 nm decreased significantly, and the absorption peak at 630 nm increased significantly; Figure 4 As shown in Figure B, r-CPDs-S has two redox reaction peaks. 2+ After that, one of the redox peaks decreased; Figure 4 From C, we can see that r-CPDs-S contains three different emission peaks, among which the wavelength interval between the blue and red emission peaks exceeds 200 nm, which requires strong orbital coupling ability to achieve electronic transition, indicating that the two emission peaks do not affect each other; Figure 4 As shown in Figure 2, the red fluorescence lifetime of r-CPDs-S is 2.28 ns. 2+After that, the fluorescence lifetime of r-CPDs-S hardly changed, indicating that the fluorescence quenching type belongs to static fluorescence quenching.
[0033] Specific embodiment 3: A method for detecting mercury ions using r-CPDs-S prepared by the method of specific embodiment 1, wherein the specific steps are as follows:
[0034] 10 μL of 10 mg / L r-CPDs-S solution and 10 μL of the sample solution were added to a cuvette containing 980 μL of ethanol. The pH of the mixed solution in the cuvette was set to 7 and the salinity was set to 25‰. The fluorescence intensity values before and after the addition of the r-CPDs-S solution to the sample solution were detected at an excitation wavelength of 530 nm and recorded as F0 and F, respectively. 2+ The linear relationship between the concentration and the fluorescence intensity ratio F0 / F is used to calculate the Hg in the sample solution to be tested. 2+ concentration.
[0035] To further optimize the detection conditions, the detection system was constructed as follows: 10 μL of 10-40 mg / L r-CPDs-S solution and 10 μL of 50 nM Hg 2+ The solution was added to a cuvette containing 980 μL of solvent, and the salinity of the solution was adjusted to 20-40‰ with NaCl. The pH value of the solution was adjusted with hydrochloric acid and NaOH solution. The addition of Hg to the r-CPDs-S solution was recorded. 2+ The fluorescence intensity values before and after the solution were recorded as F0 and F, respectively. The solvent type, r-CPDs-S concentration, water content in ethanol, pH value and salinity value were adjusted respectively, and the fluorescence intensity ratio F0 / F was used as an indicator to determine the optimal detection conditions. The results are shown in Figure 5 shown.
[0036] like Figure 5 As shown in A, other conditions remain unchanged, only the type of solvent is changed to ethanol, methanol, dichloromethane, cyclohexane, tetrahydrofuran and acetonitrile. Figure 5 From A, we can know that r-CPDs-S has a strong affinity for Hg in ethanol. 2+ Has good fluorescence response.
[0037] like Figure 5 As shown in B, other conditions remain unchanged, only the concentration of r-CPDs-S is changed. When its concentration is 10 mg / L, r-CPDs-S has a significant effect on Hg 2+ Has good fluorescence response.
[0038] like Figure 5 As shown in C, other conditions remain unchanged, only the pH is changed to 4, 5, 6, 7, 8, 9 and 10. When pH = 7, r-CPDs-S has a significant effect on Hg 2+It has a good fluorescence response. When pH ≤ 6, the fluorescence intensity and fluorescence quenching efficiency of r-CPDs-S both decreased significantly. This is because the acidic conditions destroyed the hydrogen bonds and van der Waals forces on the surface of r-CPDs-S, resulting in a decrease in the initial fluorescence intensity F0 of r-CPDs-S. When pH ≥ 8, the initial fluorescence intensity of r-CPDs-S did not change significantly, but the fluorescence quenching efficiency decreased. This is because Hg 2+ It will form a precipitate, reducing Hg 2+ Quenching efficiency of r-CPDs-S.
[0039] like Figure 5 As shown in D, other conditions remain unchanged, only the volume ratio of water to ethanol is changed, so that the volume percentage of water in the total solution is 0, 10%, 20%, 30% and 40%, respectively. When there is no water in ethanol, the r-CPDs-S has a significant effect on Hg 2+ With the increase of water content, r-CPDs-S has a good fluorescence response to Hg 2+ The fluorescence quenching efficiency decreases, which is related to the polarity of water, which will cause its aggregation quenching. Considering the application in actual liquid samples, the volume percentage of water in the total solution is about 20% as the construction of the detection system in subsequent actual samples. At this time, r-CPDs-S has a strong affinity for Hg 2+ The fluorescence response tends to be stable.
[0040] like Figure 5 As shown in Figure E, other conditions remain unchanged, only the salinity is changed to 20‰, 25‰, 30‰, 35‰ and 40‰. Under the salinity condition of 20-40‰, salinity has no obvious effect on the fluorescence quenching efficiency of r-CPDs-S.
[0041] like Figure 5 As shown in Figure F, other conditions remain unchanged and only the excitation wavelength is changed. When the excitation wavelength is 530 nm, r-CPDs-S has a higher fluorescence intensity.
[0042] Specific embodiment 4: The detection method of specific embodiment 3 is used to optimize the synthesis conditions of r-CPDs-S.
[0043] The specific synthesis method of r-CPDs-S is the same as that of the above-mentioned specific embodiment 1. The molar mass ratio of o-phenylenediamine, trimesic acid and 4-aminothiophenol, the amount of concentrated sulfuric acid added or the heating time are changed respectively. The addition amount of Hg to the r-CPDs-S solution is recorded. 2+ The fluorescence intensity values before and after the solution were recorded as F0 and F, respectively. The fluorescence intensity ratio F0 / F was used as the screening index to determine the optimal synthesis conditions of r-CPDs-S. The results are shown in Figure 6 shown.
[0044] like Figure 6As shown in A, only the molar mass ratio of o-phenylenediamine, trimesic acid and 4-aminothiophenol was changed to 1:1:1, 1:1:2, 1:1:3, 2:1:1, 2:1:2, 2:1:3, 3:1:1, 3:1:2, 3:1:3, 3:1:4, 4:1:1, 4:1:2, 4:1:3, 4:1:4. When the molar mass ratio of o-phenylenediamine, trimesic acid and 4-aminothiophenol was 3:1:2, the synthesized r-CPDs-S had a significant effect on Hg 2+ It has a good fluorescence quenching effect.
[0045] like Figure 6 As shown in Figure B, only the amount of concentrated sulfuric acid added was changed. When the amount of concentrated sulfuric acid added was 400 μL, the synthesized r-CPDs-S had a significant effect on Hg 2+ It has good fluorescence quenching effect.
[0046] like Figure 6 As shown in C, only the heating time is changed. When the heating time exceeds 6 h, the synthesized r-CPDs-S has a significant effect on Hg 2+ It has good fluorescence quenching effect.
[0047] Specific Example 5: The detection method of Specific Example 3 was used to conduct a selectivity experiment of r-CPDs-S.
[0048] Experimental method: r-CPDs-S was used to treat Hg 2+ With other metal ions Ag + , Al 3+ , Cu 2+ , Ca 2+ 、 2+ , Fe 3+ , Fe 2+ Mg 2+ , Mn 2+ 、 Zn 2+ , Cr 2+ , Hg 2+ 、 2+ 、 + and K + The fluorescence quenching response effects at the same concentration were compared, and the anion Br - , Cl - 、F - 、NO3 2- and SO4 2- In addition, in order to verify the fluorescence quenching response of r-CPDs-S to Hg 2+ Specific fluorescence response, select the same type of ions (C Hg 2+ =50 nM, C其它离子 = 250nM) for competitive inhibition experiments. The results are as follows Figure 7 shown.
[0049] Depend on Figure 7 As shown in A, in the metal cation selectivity experiment, Hg 2+ The fluorescence quenching efficiency of r-CPDs-S is significantly better than that of other metal cations, with the F0 / F value reaching 2.4. Other metal ions have no obvious effect on the fluorescence intensity of r-CPDs-S.
[0050] Depend on Figure 7 As shown in Figure B, in the metal cation competition experiment, even under high concentration of interfering metal ions, r-CPDs-S still has a strong affinity for Hg 2+ It has high specific recognition ability, while other interfering ions have high specific recognition ability for r-CPDs-S / Hg 2+ There was no significant effect on the fluorescence quenching.
[0051] Depend on Figure 7 As shown in Figure 3C, in the anion selectivity experiment, other anions had no obvious effect on the fluorescence intensity of r-CPDs-S.
[0052] Depend on Figure 7 As shown in Figure 2, in the anion competition experiment, even under high concentration of interfering anions, r-CPDs-S still has a strong affinity for Hg 2+ It has high specific recognition ability, while other interfering ions have high specific recognition ability for r-CPDs-S / Hg 2+ There was no significant effect on the fluorescence quenching.
[0053] Figure 8 A in the figure shows the fluorescence color change of r-CPDs-S solution under 365 nm UV light after adding different metal ions. 2+ When ions were added, the fluorescence intensity of r-CPDs-S decreased, and there was no significant change in the fluorescence intensity when other metal ions were added. Figure 8 As shown in B, Hg 2+ The color of the r-CPDs-S solution changed from pink to blue, and there was no obvious change in the color of the solution when other metal ions were added.
[0054] The above results show that r-CPDs-S has a great influence on Hg 2+ It has high selectivity and does not affect the r-CPDs-S sensor for Hg under the interference of various metal ions and anions. 2+ The detection effect shows that the r-CPDs-S sensor has strong anti-interference ability and has good application prospects even in complex environments.
[0055] Specific Example 6: Using the detection method of Specific Example 3 to detect Hg 2+ Sensitivity determination.
[0056] Standard curve drawing: configure 0, 1.0, 2.0, 5.0, 8.0, 10.0, 20.0, 40.0, 50.0 nM Hg 2+ Solution, take 10 μL of different concentrations of Hg 2+ The solution and 10 μL of 10.0 mg / L r-CPDs-S solution were added to a cuvette containing 980 μL of ethanol solution. 2+ The standard curve is drawn with the concentration as the horizontal axis and the fluorescence intensity ratio F0 / F as the vertical axis. The results are as follows Fig. 9 shown.
[0057] Depend on Fig. 9 Different concentrations of Hg were added to A 2+ The fluorescence intensity change results of r-CPDs-S show that Hg 2+ The fluorescence intensity of r-CPDs-S at 595 nm and 645 nm increased with the concentration of Hg in the range of 1.0-50.0 nM. 2+ The concentration increases and decreases. Fig. 9 The fluorescence intensity ratio of B in F0 / F is similar to that of Hg 2+ The linear regression curve of Hg 2+ The concentration has a good linear relationship in the range of 1.0-50.0 nM, and the linear equation is y = 1.10509+0.03494x, R 2 = 0.9835, the detection limit is calculated to be 0.19 nM, where y is the fluorescence intensity ratio and x represents Hg 2+ concentration.
[0058] Fig.10 From A, we can see that Hg 2+ In the concentration range of 1.0-40.0 nM, r-CPDs-S / Hg 2+ The color changes from pink to blue in sunlight. Fig.10 From B, we can see that Hg 2+ In the concentration range of 1.0-40.0 nM, r-CPDs-S / Hg 2+ Under 365 nm ultraviolet light, the fluorescence intensity gradually decreased.
[0059] In summary, the detection method of specific embodiment 3 is used to detect Hg 2+ The detection results showed that the method had a low detection limit and a wide detection range, indicating that the method had good practicability in actual samples.
[0060] Specific embodiment 7: The mercury ions in the actual sample are detected by the detection method of specific embodiment 3, including the following steps:
[0061] Step 1: Sample pretreatment:
[0062] Liquid sample pretreatment: Seawater samples were collected from the coastal waters of Ningbo and stored in glass bottles. The seawater samples were filtered through a 0.22 μm filter membrane to remove particulate matter and microorganisms to obtain the sample solution to be tested, which was stored in a 4°C refrigerator for later use;
[0063] Solid sample pretreatment: Abalone, razor clams and oysters were all from the local seafood market in Ningbo.
[0064] 5 g of solid sample was homogenized after cell disruption, and 30 mL of ultrapure water and 10 mL of acetonitrile were added in sequence, vortexed for 3 min, and then 10 g of NaCl was added and ultrasonicated for 3 min. 3 The mixture was centrifuged at 4 °C for 10 min, and the aqueous layer was collected to obtain the sample solution to be tested, which was then stored in a refrigerator at 4 °C.
[0065] Step 2: Detection of sample solution:
[0066] The sample solution was tested using the detection method of the specific embodiment 3, only 980 μL of ethanol was changed to 780 μL of ethanol and 200 μL of the sample solution, and other conditions remained unchanged. The fluorescence intensity values before and after the r-CPDs-S solution was added to the sample solution were recorded. 2+ The effectiveness and practicality of the test were tested by ICP-MS and the above test method on seawater, abalone, razor clam and oyster samples. No Hg was detected in the above test sample solutions by ICP-MS. 2+ , and then the spike recovery experiment was carried out, as shown in Table 1.
[0067] Table 1 Hg in actual samples determined by r-CPDs-S 2+ (n=3)
[0068]
[0069] The results are shown in Table 1. In seawater samples, the spike recovery was 98.8%-101.6%, with RSD ≤ 0.7%. In addition, in shellfish samples, the spike recovery was 92.6%-106.0%, with RSD ≤ 2.7%, which indicates that this method is effective for detecting trace Hg in seawater and shellfish tissue samples. 2+ The analysis was performed with high accuracy and precision.
[0070] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.
Claims
1. A method for preparing a sulfur-doped near-infrared carbonized polymer for detecting mercury ions, characterized in that The specific steps are as follows: 1-4 mmol o-phenylenediamine, 1 mmol trimesic acid and 1-4 mmol 4-aminothiophenol are dissolved in 12 mL deionized water, and then 200-600 μL concentrated sulfuric acid is added. After ultrasonication at 40 Hz for 2-3 min, the mixture is transferred to a polyethylene tetrafluoro liner and placed in an autoclave. After heating at 200-230° C. for 6-8 h, the autoclave is naturally cooled to room temperature, and then unreacted impurities are removed by continuous dialysis using a 1000 Da dialysis bag for 24-48 h. The mixture is then placed at a temperature of -20-30° C. and a pressure of -0.1-0.01 Pa and freeze-dried for 24-48 h to obtain black particles, which are sulfur-doped near-infrared carbonized polymers for detecting mercury ions, wherein the molar mass ratio of the o-phenylenediamine, the trimesic acid and the 4-aminothiophenol is 3:1:
2.
2. The method for preparing a sulfur-doped near-infrared carbonized polymer for detecting mercury ions according to claim 1, characterized in that: The amount of concentrated sulfuric acid added is 400 μL.
Citation Information
Patent Citations
Carbon dot with aggregation-induced emission characteristic and multi-component detection of Hg < 2 + >, Cu < 2 + > and BSA
CN117467436A
Preparation method and detection application of near-infrared carbonized polymer for detecting copper ions
CN117658109A